Hope, bias and survival expectations of advanced cancer patients: A cross‐sectional study. Issue 5 (1st April 2021) - Finkelstein, Eric A.; Baid, Drishti; Cheung, Yin Bun; Schweitzer, Maurice E.; Malhotra, Chetna; Volpp, Kevin; Kanesvaran, Ravindran; Lee, Lai Heng; Dent, Rebecca Alexandra; Ng Chau Hsien, Matthew; Bin Harunal Rashid, Mohamad Farid; Somasundaram, Nagavali
Abstract: Objective: Many patients with advanced illness are unrealistically optimistic about their prognosis. We test for the presence of several cognitive biases, including optimism bias, illusion of superiority, self‐deception, misattribution, and optimistic update bias, that could explain unrealistically optimistic prognostic beliefs among advanced cancer patients and quantifies the extent to which hope exacerbates these biases. Methods: A cross‐sectional survey was administered to 200 advanced cancer patients with physician‐estimated prognoses of one year or less. Hope was measured using the Herth Hope Index (HHI). Hypotheses were tested using linear and logistic regressions and a structural‐equation model. Results: Results are consistent with the presence of optimism bias, illusion of superiority, self‐deception, and misattribution. All of these biases are amplified by higher levels of hope. Each 1‐point higher HHI is associated with a 6% (OR: 1.06; 95% CI: 1.01–1.11) greater odds of believing their illness is curable, a 0.33‐year (95% CI: 0.17–0.49) longer expected survival, a 6% (OR: 1.06; 95% CI: 1.02–1.11) higher probability of believing that survival outcomes are better than the average patient, a 5% higher odds of believing primary intent of treatment is curative (OR: 1.05; 95% CI: 1.00–1.10), and a 12% (OR: 1.12; 95% CI: 1.05–1.17) higher odds of believing they are well‐informed. Mediation analyses revealed that hope significantly mediates the effect of mental‐well‐being and loneliness on expected survival. Conclusions: Results suggest advanced cancer patients succumb to several cognitive biases which are exacerbated by greater levels of hope. As a result, they are susceptible to possible over‐treatment and regret.